Biomass gasification, pyrolysis and torrefaction : practical design and theory - Basu, Prabir, 1946- (Academic Press, imprint of Elsevier, 2018)
"Biomass Gasification, Pyrolysis and Torrefaction, Third Edition, is enhanced with a new topic on processing and cleaning of product gas of gasification and a brief introduction to biomaterials, making it a versatile resource that not only explains the basic principles of energy conversion systems, but also provides valuable insight into the design of a complete biomass conversion systems. With a dedicated focus on the design, analysis and operational aspects of biomass gasification, pyrolysis and torrefaction, this edition offers comprehensive coverage of biomass in its gas, liquid or solid states in a single accessible source. The author provides many worked design problems, step-by-step design procedures and real data on commercially operating systems. Although the book carries the name 'biomass', the bulk of its content is also applicable to non-biomass fuels like coal, petcoke, municipal solid waste and others. This book will help engineers, scientists and operating personnel of biomass gasification, pyrolysis or torrefaction plants, gain better comprehension of the basics of biomass conversion. Biomass Gasification, Pyrolysis and Torrefaction, Third Edition, is enhanced with a new topic on processing and cleaning of product gas of gasification and brief introduction to biomaterials making it a versatile resource that not only explains the basic principles of energy conversion systems, but also provides valuable insight into the design of a complete biomass conversion systems. With a dedicated focus on the design, analysis, and operational aspects of biomass gasification, pyrolysis, and torrefaction, this edition of the book offers comprehensive coverage of biomass in its gas, liquid, or solid states in a single easy-to-access source. The author provides many worked out design problems, step-by-step design procedures and real data on commercially operating systems. Although the book carries the name 'biomass', the bulk of its content is also applicable to non-biomass fuels like, coal, petcoke, municipal solid waste and others. This book will allow professionals, such as engineers, scientists, and operating personnel of biomass gasification, pyrolysis or torrefaction plants, to gain a better comprehension of the basics of biomass conversion. Features updates with the most recent research and technologyExpanded to include a new chapter on syngas purification Contains step-by-step process flow diagrams, design data, conversion charts and numerical examples with solutions Provides available research results in an easy-to-use design methodology Examines the economic aspects of biomass conversion"--